Ischemic preconditioning improves resistance training session performance - da Silva Novaes, J.; da Silva Telles, L. G.; Monteiro, E. R.; da Silva Araujo, G.; Vingren, J. L.; Silva Panza, P.; Reis, V. M.; Laterza, M. C.; Vianna, J. M. (The Journal of Strength and Conditioning Research, 2021)
The aim of this study was to investigate the acute effect of ischemic preconditioning (IPC) in a resistance exercise (RE) training session on the number of repetitions performed, total volume, and rating of perceived exertion in recreationally trained and normotensive men. Sixteen recreationally trained and normotensive men completed 3 RE sessions in a counterbalanced and randomized order: (a) IPC protocol using 220 mm Hg followed by RE (IPC), (b) IPC cuff control protocol with 20 mm Hg followed by RE (CUFF), and (c) no IPC (control) followed by RE (CON). RE was performed with 3 sets of each exercise (bench press, leg press, lateral pulldown, hack machine squat, shoulder press, and Smith back squat) until concentric muscular failure, at 80% of one repetition maximum, with 90 seconds of rest between sets and 2 minutes of rest between exercises. Ischemic preconditioning and CUFF consisted of 4 cycles of 5 minutes of occlusion/low pressure alternating with 5 minutes of no occlusion (0 mm Hg) using a pneumatic tourniquet applied around the subaxillary region of the upper arm. For each condition, the number of repetitions completed, total volume of work performed, and rating of perceived exertion were determined. No significant difference was found for rating of perceived exertion between any experimental protocol. Ischemic preconditioning significantly (p < 0.05) increased the number of repetitions across exercises. Consequently, total volume performed (sum of total number of repetitions x load for each exercise) was significantly higher in IPC (46,170 kg) compared with CON (34,069 kg) and CUFF (36,590 kg) across all exercises. This work may have important implications for athletic populations because it demonstrates increase in muscle performance outcomes during a single RE session. Therefore, performing IPC before RE could be an important exercise prescription recommendation to increase maximum repetition performance and total volume of work performed and thus potentially increase desired training adaptations (i.e., strength and hypertrophy).